(untitled) (Indian Journal of Child Health, 2020)
Introduction: Mothers suffer disturbed sleep caused by the nocturnal patterns of breastfeeding. Skin-to-skin care (SSC) between mothers and babies has known comforting effects on mother and baby. Aim: The aim of the study was to examine the effect of daily practice of SSC in the 1st weeks after delivery in assisting mothers to adapt to the sleep patterns of her baby. Materials and Methods: This is a prospective cohort study of 90 breastfeeding mothers and their infants who were followed up from birth for 6 weeks. They were randomly divided into three groups: 30 performed SSC only at birth, 30 continued SSC on a daily basis, and 30 controls. Child development and weight gain were assessed at 6 weeks using Denver scale and maternal post-partum depression by the Beckwith depression tool. Sleep, activity, fatigue, appetite, health, and sex status were derived from the tool and correlated to parameters under study. Results: At 6 weeks, mother’s satisfaction with sleep, depression score, child’s weight gain, and development were significantly improved in the intervention group. Sleep correlated with activity, less fatigue (r0.5 at p=0.000), appetite (r0.4, p=0.001), and sex (r0.3, p=0.004) but not with maternal weight loss or health (p>0.05). Maternal sleep, activity, less fatigue, and appetite were positively correlated with child development at p=0.000, but not infants’ weight gain (p>0.05). Conclusions: Daily SSC in the early weeks can support adaptation of mother to her infant’s night feeds, promotes child growth and development and maternal well-being.